Principal Leadership in Improving Teacher Performance - Aulia Ramdanu; Abdul Hayyie Al Kattani; Wido Supraha (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The purpose of this study is to describe the leadership of the principal as a leader and manager in schools at SDN 01 Pagi, Central Jakarta. This study uses a descriptive qualitative approach. The participant in this research is the principal of the school. Data collection techniques with observation, interviews and documentation. The results show that the principal in carrying out his duties and functions uses a democratic leadership style. As a leader and manager, the principal is able to create a conducive atmosphere between teachers who have different school origins, build cooperation with parents in participating in maintaining and developing schools, providing facilities to improve information technology capabilities for their subordinates.